What's in a face? The impact of nonlinguistic 'ethnic' facial features on accent perception. Issue 10 (26th November 2019) - Eisenchlas, Susana A.; Michael, Rowan B.
ABSTRACT: Sociolinguistic research on language attitudes has revealed that non-standard accented speakers are usually perceived more negatively than members of the dominant speech community. Few studies, however, have examined whether a speaker's ethnicity, evidenced by nonlinguistic factors such as appearance, may play a role in listeners' perception of accent. This project is based on studies by Rubin (1992. "Nonlanguage factors affecting undergraduates' judgments of nonnative English-speaking teaching assistants." Research in Higher Education 33 (4): 511–531. http://www.jstor.org/stable/401960471992 ) investigating perceptions of foreign academics by undergraduate students in the US. In those studies, participants listened to a short lecture presented with a projection of either a Caucasian or a Chinese face and completed a listening comprehension test and a speakers' evaluation rating scale. Unknown to the participants, the recording was produced by a single standard American-English speaker. Participants exposed to the Chinese face perceived a non-standard accent and rated the speaker more negatively than those exposed to the Caucasian face. Our present study extends Rubin (1992) by examining data collected through an online survey from languages and linguistics university students in Australia. Unlike Rubin's (1992) findings, this study found no statistically significant differences between responses based on exposure to a Chinese or Caucasian face, a fact that could be attributed primarily to the multilingual and multicultural composition of Australian universities.